The use of data in decision making for school-based social work - Robert Lucio; Michael Campbell; Michael S. Kelly (International Journal of School Social Work, 2020)
Industries are increasingly taking advantage of the access provided in the digital age to use data to inform business and practice-based decision making. The profession of social work has recently called for social workers to become more data-driven, through its Grand Challenge to leverage technology such as data-driven decision making for social good. School-Based Social Workers, who often work in educational contexts that demand they collect and use data are being asked to figure out ways to engage data to help promote evidence-informed practices and process level changes. Using a scoping review, this article looks at the state of the current literature on how this process is evolving. This information can help set the stage for a framework for the systematic application of data in social work settings.
Keywords: School-Based Social Work; School Social Work; Evidence-Informed Decision Making; Scoping Review